America's Use of Terror : From Colonial Times to the A-bomb - Huggins, Stephen (Stephen Richard), 1943- (Book collections on Project MUSE., 2019)
""Terrorism" is generally defined as the unlawful use of violence and intimidation, especially against civilians, as a means to achieve political aims. American Exceptionalism--the belief that we are morally better than other nations, a "shining city on a hill" whose beams radiate into the world--precludes that we would engage in that kind of behavior. Doesn't it? Stephen Huggins doesn't think so. In America's Use of Terror he argues that, although Americans view themselves as the victims of terrorism and their political leaders disparage terrorist acts as cowardly and despicable, the United States has historically used acts of violence against noncombatants to induce terror and further its political objectives. He investigates historical examples from the Colonial period through World War II that illustrate the conflict between the United States' claims of exceptional moral standards and its frequent use of terror to influence civilian behavior. Huggins claims that the tension between the United States' supposed disdain for terror and its frequent use of it is "a coarse thread of hypocrisy" running through our nation's history"--